Photoresponsive Electrodes Modified with DNA Duplexes Possessing a Porphyrin Dimer. Issue 72 (28th November 2017) - Takada, Tadao; Iwaki, Toshihiro; Nakamura, Mitsunobu; Yamana, Kazushige
Abstract: This work describes the formation of a porphyrin (Por) dimer using a DNA duplex as a scaffold and photocurrent generation from electrodes modified with a monolayer of Por–DNA conjugates. The solid‐phase click reaction between an azide‐porphyrin and oligonucleotide labeled with an ethynyl group on CPG support was utilized to conjugate the Por to the DNA. UV/Vis absorption and circular dichroism (CD) spectral studies revealed that the Por dimer can be formed through DNA hybridization and that through‐space electronic interactions, characterized from the exciton‐coupled absorption and the bisignate CD, can occur between the two Por molecules. Photoelectrochemical experiments were performed for the electrodes functionalized with a monolayer composed of the Por–DNA conjugates. It was found that the Por dimer on the electrode, which was designed to resemble the special pair in natural photosynthesis, shows efficient photocurrent generation in the presence of electron‐acceptor reagents compared with the Por monomer. These findings strongly support the idea that the DNA structures could be useful to construct Por arrays, which is essential for the design of photo‐ and bio‐electronic devices. Abstract : DNA‐porphyrin electrodes : A porphyrin (Por) dimer on an electrode (see figure), which was designed to resemble the special pair in natural photosynthesis, shows efficient photocurrent generation in the presence of electron acceptor reagents compared with the Por monomer. The results support the idea that DNA structures could be useful for the construction of Por arrays, which is essential for the design of photo‐ and bio‐electronic devices.